Petrography and zircon morphology of syntectonic granitoids rocks of Hafafit area, South Eastern Desert (Egypt). - Thabet, I.; Kilias, A.; Koroneos, A.; Kamh, S. (Bulletin of the Geological Society of Greece, 2013)
The study deals with the petrography of the granitoid rocks intruding the five (A to E) domes of Hafafit Culmination. The morphological characteristics of zircon crystals are also examined, in order to elucidate the genesis of zircon and their host Hafafit granitoids. The granitoid rocks are tonalites, granodiorites and quartz diorites, all exhibiting gneissic texture. The zircon crystals from all the rock types intruding each one of the domes are examined in detail for colour, inclusions, crystal length, crystal width, elongation ratio, crystal form and habit, degree of roundness and corrosion, and are distinguished in groups on the basis of the previous characteristics. Two generations of zircons have been recognized; the first generation with magmatic features and the second one with post magmatic features. The first generation of zircon is attributed to the subduction, magmatic and deformation events while the second generation of zircon is attributed to metamorphism.